Validity and reliability of willingness-to-pay estimates: Evidence from two overlapping discrete-choice experiments - Harry Telser; Karolin Becker; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2008)
Discrete-choice experiments, while becoming increasingly popular, have rarely been tested for validity and reliability. This contribution purports to provide some evidence of a rather unique type. Two surveys designed to measure willingness-to-accept (WTA) for reform options in Swiss health care and health insurance are used to provide independent information with regard to two elements of reform. The issue to be addressed is whether WTA values converge although the three overlapping attributes (a more restrictive drug benefit, a delayed access to medical innovation, and a change in the monthly insurance premium) are embedded in widely differing choice sets. Experiment A contains rather radical health system reform options, while experiment B concentrates on more familiar elements such as copayment and the benefit catalogue. While mean WTA values differ between experiments, they tend to vary in similar ways, suggesting at least theoretical validity and reliability.
Keywords: C35; C93; I11; 330; willingness-to-pay; discrete choice experiments; validity; reliability; framing effects; Willingness to pay; Qualitatives Verfahren; Diskrete Entscheidung